Bridge Capture permits cost-efficient, rapid and sensitive molecular precision diagnostics - Adamusová, Simona; Korkiakoski, Anttoni; Laine, Nea; Musku, Anna; Rantasalo, Tuula; Kim, Jorma; Blomster, Juuso; Laine, Jukka; Hirvonen, Tatu; Pursiheimo, Juha-Pekka; Tamminen, Manu (Elsevier, 2026)
Liquid biopsies quantifying mutations in circulating-tumor DNA (ctDNA) by targeted next-generation sequencing have been gaining popularity. They are performed by various library preparation methods, each with distinct advantages and limitations. This work introduces Bridge Capture, a novel technology that goes beyond the advantages of market-leading liquid biopsy technologies, eliminating the need to compromise between scalability, cost-efficiency, sensitivity or panel size. Twenty-four matched contrived colorectal biospecimens mimicking ctDNA were analyzed by Bridge Capture, Archer LIQUIDPlex and AmpliSeq CHPv2 for Illumina to compare variant allele frequency (VAF) detection. Bridge Capture was evaluated for sequencing depth requirement, inter-lab reproducibility, automatization and panel scalability. Of all methods, Bridge Capture detected the lowest VAF and all VAFs strongly correlated with Archer LIQUIDPlex (R2 = 0.995) and AmpliSeq CHPv2 for Illumina (R2 = 0.988). Owing to its unique design, the Bridge Capture is compatible with the commonly used next-generation sequencing platforms and effectively utilizes sequencing capacity, permitting affordable and sensitive variant detection. The method demonstrated high reproducibility across independent laboratories and between automated and manual workflow. The panel size was increased by 300% and had negligible impact on performance and cross-reactivity of the probes implying high multiplexing capabilities. Taken together, Bridge Capture is a cost-efficient, simple, rapid and sensitive cancer diagnostics tool that has a potential to significantly improve the detection of mutations.